Efficacy and Safety of Immunotherapy with Interferon-Gamma in the Management of Chronic Sulfur Mustard-Induced Cutaneous Complications: Comparison with Topical Betamethasone 1% - Yunes Panahi; Amirhossein Sahebkar; Seyyed Masoud Davoudi; Mojtaba Amiri; Fatemeh Beiraghdar (The Scientific World Journal)
The present trial investigated the efficacy of immunotherapy with interferon-gamma (IFN-γ) in the treatment of sulfur mustard (SM)-induced chronic skin complications. Forty subjects who were suffering from chronic skin complications of SM and were diagnosed to have severe atopic dermatitis, were assigned to IFN-γ (50 μg/m2) subcutaneously three times per week (n=20) or betamethasone valerate topical cream 0.1% (n=20) every night for 30 days. Extent and intensity of cutaneous complications was evaluated using scoring atopic dermatitis (SCORAD) index, and quality of life using dermatology life quality index (DLQI) at baseline and at the end of trial. SCORAD-A and SCORAD-B scores were significantly decreased in both IFN-γ and betamethasone. However, SCORAD-C score was decreased only in the IFN-γ group. There were significant reductions in overall as well as objective SCORAD scores in both groups. As for the magnitude of changes, treatment with IFN-γ was associated with greater reductions in overall, objective and segmented SCORAD scores compared to betamethasone. DLQI reduction was found to be significantly greater in the IFN-γ group. Promising improvements in quality life and clinical symptoms that was observed in the present study suggest the application of IFN-γ as an effective therapy for the management of SM-induced chronic skin complications.